Scientific production on the marketing communication: a bibliometric review from 1985 to 2022 - Fernández-Alonso, Yordanis de la Caridad; Ortiz-Pérez, Olga Lidia; Barroso Grave de Peralta, George; Hernández-Carreón, Nadia Vianney (Bibliotecas. Anales de investigación, 2024)
Objective. The present manuscript focused on the analysis of scientific production on marketing communication in the tourism industry in the period from 1985 to 2022. Design/Methodology/Approach. A descriptive bibliometric study was carried out to classify and analyze scientific production on the basis of indicators. The processing and analysis of the information was made possible with the use of Rstudio.cloud and Endnote X9 software. Results/Discussion. The results show that the year 2022 was the year with the highest scientific output, the Journal of Travel and Tourism Marketing, and the countries USA and Australia contain the highest number of scientific publications, and Maja Šerić is the most prolific author. The strongest lines of cooperation are between Australia, China, Spain and the USA. Marketing communication, social media, integrated marketing communication and destination image and sustainable tourism are the topics most addressed by researchers along with the impacts caused by Covid-19. Conclusions. The study provides valuable information to the research field by presenting a vision of marketing communication in tourism that can guide future researchers in their search for new research. Originality/Value. It provides an overview of marketing communication in tourism based on the above-mentioned indicators and offers important data as an information resource for decision making by managers and academics in research, projects and investments.